Dye Removal from Wastewater Using Iron Salts - Al-Hemiri, Adil; Al-Anbari, Hameed; K. Shakir, Ibtihal (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
This investigation was carried out to study the treatment and recycling of wastewater in the cotton textile industry for an effluent containing three dyes: direct blue, sulphur black and vat yellow. The reuse of such effluent can only be made possible by appropriate treatment method such as chemical coagulation. Ferrous and ferric sulphate with and without calcium hydroxide were employed in this study as the chemical coagulants.The results showed that the percentage removal of direct blue ranged between 91.4 and 94 , for sulphur black ranged between 98.7 and 99.5 while for vat yellow it was between 97 and 99.